Kekerasan Diskursif dalam Rekonstruksi Tubuh Samurai pada Era Meiji - Anwar, Khairil; Azhariyah, Ayu (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2026)
This study examines the discursive architecture of modern Japanese subjectivity as reflected in the writings of Tokutomi Sohō in the influential magazine Kokumin no Tomo (1887–1898). Employing Norman Fairclough’s model through three dimensions of analysis—text, discursive practice, and social practice—this study examines how Tokutomi Sohō’s heiminshugi discourse in Kokumin no Tomo functions as a discursive strategy for the construction of modern Japanese masculinity. The findings reveal three key points: (1) the symbolic delegitimization of the samurai class (shizoku) as gokubushi as a mechanism for reconstructing a new masculinity based on economic productivity; (2) a biopolitical shift from the glorification of ritual death (seppuku) toward economic vitality as the marker of ideal masculinity; and (3) the transformation of this productive masculinity into an imperialist force in the aftermath of the Sino-Japanese War (1895). This study concludes that the discourse of heiminshugi is not merely a political ideology, but a technology of power that disciplines the bodies of Japanese men—freeing them from feudal shackles only to bind them to the imperatives of the nation-state and the agenda of imperialism.